Application of geo-information technologies in determining the depth of earthquake in the Monte Nerone district (Marche district, Nothern Apennines in 1781) - Vyzhva, S.; Zatserkovnyi, V.; Zobniv, I.; De Donatis, M.; Tsiupa, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the work, the main fault of the Monte Nerone anticline (Marche – Northern Apennines) was investigated, as well as the study, identification and fixation of faults: the normal fault system in the Monte Nerone area and the search for correlations on the ground of the Monte Nerone fault with the earthquake in the Marche Apennines in 1781. A small-angle eastern normal fault dipping at a small angle in the structure of extensive deformations was interpreted, it was based on the seismic profiles of the crust. Therefore, seismic events registered in this tectonically active zone can be related to this fault, as, for example, recent events in the area of the southern UmbrianMarchean Apennines. The main local tectonic structure is an anticlinorium, oriented in NW-SW, corresponding to the regional Apennine depression, with a longitudinal extension of about 30 km and a wavelength of 5–6 km. The work on sounding the Monte Nerone main fault was developed in several stages: project preparation, terrain surveying, data processing and synthesis. The project included a CTR of the Marche region, a geodetic reference map based on the international ellipsoid centered on Monte Mario (Rome 1940), a geological map at a scale of 1:10 000 and satellite orthophoto plans of the reference areas. Reference layers were created in the work in the form of a shape file to be able to catalog and share the information obtained in the field. These layers included: metadata, data containing measurements, annotation. During the fieldwork, a route and stops were planned where more detailed measurements were made and played the role of landmarks for checking with previously obtained data to confirm or refute the hypothesis. In the route, nine main stops were selected, where reconnaissance of the territory was carried out, geological characteristics of the formation were determined, measurements and recording of the main fault, its direction, angles of dip and extension, slope were carried out. All measurements were recorded in the software environment and previously created database. Using a Bluetooth GPS connected to a tablet PC, accurate tracking of the position where the measurements were made was obtained. With the help of the measurements carried out, it was possible to put forward the hypothesis that the Monte Nero fault extends from the west, starting from La Valle, crossing the western, southern and eastern slopes of Monte Nerone and extending to Monte La Montagnola, continuing to Pietralunga on its entire along the length of about 9.9 km. In addition, having the CTR with the geological map, we were able to confirm certain geological deposits. A 3D terrain model was created in ArcScene software to fully account for the terrain situation. The topography of the area was modeled in relation to the geological situation, the fault was marked, and the collected data were interpreted. Given the 54° dip, 90° inclination of the rocks we measured along the route, it can be assumed that the earthquake was shallow, with a maximum depth of about 10 km.
Keywords: GIS; GPS; CTR; structure-from-motion; 3D modelling; historical earthquake; instrumental seismicity; extensional tectonics